Zagadnienie myślenia i odpowiedzialności w filozoficznej refleksji Hannah Arendt - Szary, Stefan (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The problem of responsibility became, particularly in the second half of the twentieth century, one of the most important subjects of philosophical reflection. Many thinkers, including Martin Heidegger, Emmanuel Lévinas, Karl Jaspers and Hans Jonas, expressed their views about it. The evil of totalitarian systems became the main experience triggering discussion about responsibility. The reflection included in Hannah Arendt’s works is an important voice in the debate and it remains up-to-date despite the passage of time. Arendt demonstrated the multidimensional and dramatic character of responsibility by presenting the meanings of vita contemplativa and vita activa in reference to every person’s existence. The thinker was searching for the answer to the question about the essence of responsibility. Today, she still introduces the readers of her works and the listeners of numerous interviews she gave to a more profound understanding of responsibility-related experiences. In my humble opinion, the greatest value of philosophical interpretation of Hannah Arendt’s works is the fact that they still remain constructive reflections. Their influence is not limited to shaping one’s mind only. It goes deeper and develops our attitudes, including the attitude to properly understood responsibility.